Linking human resource training and development, employee commitment and job satisfaction: The moderation role of the work environment - Abel Gebremedhn Desta (Research Synergy Foundation, 2021)
The main purpose of this article was to investigate the link between human resource training and development, employee commitment and job satisfaction, and the moderation role of the work environment. The quantitative research design was adopted using 212 valid questionnaires that were filled by selected private banks in Addis Ababa, Ethiopia using a convenience sampling technique. To validate the factor structure of the observed variables confirmatory factor analysis was applied and Structural Equation Modeling was used to test the hypothesized relationship. The results showed that training and development positively relate to organizational employee commitment and employee job satisfaction of workforces, while the work environment positively moderates this relationship. This implies that investing in human resource training and development positively affects the employee’s commitment to the organization and enhances their satisfaction. The more the work environment is conducive the better the relationship between the study variables. Finally, the implication, limitations, and future studies were discussed. Keywords: Training and Development, Commitment, Work Environment. Job Satisfaction